High-cited publications from the indian orthopedic research in the last two decades - Abhishek Vaish; Raju Vaishya; B M Gupta; Mallikarjun Kappi; Shuchi Kohli (Apollo Medicine)
Objective: The high-cited publications (HCPs) (with 50 or more citations) on orthopedic research from India were analyzed on various parameters. Methodology: The HCPs that were published between 2002 and 2021, on the Indian orthopedic research and indexed in the Scopus database were evaluated on various parameters. A network analysis was used to evaluate and visualize the collaborative interaction among the most productive organizations, authors, and keywords using VOSviewer and Biblioshyn software. Results: Of the total 4606 publications, 179 (3.88%) were HCPs, that were cited 22767 times (averaging 127.19 citations per publication). An external funding was received in 24.58% of publications and 36.87% of publications had an international collaboration. The most productive organizations were the Indian Institute of Science – Bengaluru (n = 11), All India Institute of Medical Sciences – New Delhi, and Amrita Institute of Medical Sciences – Kochi (n = 8 each) and the most impactful organizations in terms of citations per paper and relative citation index were Vellore Institute of Technology – Vellore, TIET – Patiala, and Lovely Professional University. The most productive authors were K. Chatterjee, D. Lahiri, and R. Vaishya. The most impactful authors were P. Mukherjee, S. Rajasekaran, and J. N. Babu in terms of citations per paper and relative citation index. Delhi was the epicenter of research and publications (n = 27). Material science and medicine contributed the largest number of publications (n = 77 and n = 73), followed by Engineering (n = 51). Treatment and clinical studies accounted maximally (24.58% and 8.38%) and hydroxyapatite (n = 40) was the most significant keyword appearing in the literature. Conclusion: This study provided an insight into understanding of research status including trends identified and studied the most influential contributions and performance of Indian organizations and authors and indicated broad and narrow subject fields contributing to this medical specialty. It gives some ideas about past, present, and future hotspots in research.